Novel Capability-Based Risk Assessment Calculator for Construction Contractors Venturing Overseas - Wang, Chen; Loo, Siaw Chuing; Yap, Jeffrey Boon Hui; Abdul-Rahman, Hamzah (American Society of Civil Engineers, 2019)
Globalization creates opportunities for contractors to enter lucrative international markets yet international projects are exposed to more diverse and complex risks than domestic projects. Owing to vast uncertainties and complexities, international construction entry decisions are intricate. Although conventional Probability-Impact (P-I) risk models are useful, the firm's capabilities are missing in early assessments for project selection decision. Hence, this study aims to develop a capability-based risk assessment (CapRA) calculator for international contractors venturing overseas. The international construction firm's capabilities are explored using resource-based views, dynamic capabilities, and Porter's generic value chain theories to conceptualize an integrated framework for risk assessment. Additionally, a questionnaire was sent to international construction firms operating outside their home countries to appraise their firm's capabilities and international construction project risk significance values. Then, a partial least squares approach was used to analyze the data. The findings are used to develop a novel CapRA model, which is then formulated into modified P-I risk model equations and computerized into a CapRA calculator to simplify the application. In essence, this study contributes to both knowledge and practice by developing and testing a model to improve the accuracy and facilitate project selection decisions for international construction firms. © 2019 American Society of Civil Engineers.